Efficacy of an herbal antioxidant as an adjunct to nonsurgical periodontal therapy on procalcitonin levels in smokers with chronic periodontitis - M V N Sravya; Rekha Rani Koduganti; Veerendranath Reddy Panthula; Prasanna Jammula Surya; Himabindu Gireddy; Rajashree Dasari; Manasa Ambati (Wolters Kluwer Medknow Publications, 2019)
Context: Smokers are at a higher risk of contracting periodontitis. This association is established and reported in many studies. Periodontitis is a polymicrobial disease, wherein smoking is an environmental factor which aggravates the damage caused to the tissues. Procalcitonin (ProCT) is a well-known marker for inflammatory and other infectious diseases and has been assessed in this study. It has been observed that the release of reactive oxygen species (ROS) is exaggerated in smokers. Antioxidants are administered to combat the harmful effects caused by the ROS, and Oxitard™ is a powerful herbal antioxidant that can counteract the action of free radicals. Aims: As smokers are more prone to tissue injury due to excessive release of ROS, this study aimed to understand the benefits of systemic administration of Oxitard after scaling and root planing (SRP) on serum ProCT levels in smokers with chronic periodontitis (CP). Settings and Design: This was a randomized interventional study, wherein forty patients participated. Materials and Methods: Forty smokers with CP aged, between 35 and 60 years, were equally divided into Group A (SRP + Oxitard) and Group B (SRP only), selected from an outpatient ward of a referral care hospital in Hyderabad. A written informed consent was obtained from all the patients, and the study was approved by the institutional ethical committee (DN0026-15). Statistical Analysis Used: Data were analyzed by GraphPad Prism software version 6.01 (GraphPad software incorporation, California, USA). Comparison within the groups was made by paired t-test and between the groups by unpaired t-test. P < 0.05 was considered of statistical significance. Results: Intragroup assessment showed an improvement in all the variables from baseline to 3 months, which was statistically significant (P < 0.0001). A comparison between the groups, however, yielded better results in Group A (Oxitard + SRP) over Group B. Conclusions: Oxitard administered systemically for 3 months after SRP was beneficial in improving both clinical and biochemical parameters.